P4_3 - It's a Mad Lego World - Garner, James; Byworth, Kayleigh; Lawrence-Morgan, Dennis; Rowe, Ryan (Physics Special Topics, 2022)
In this paper, we investigate what would happen to the orbital radius of the Moon if the Earth was made of Lego. We found that for an Earth of equal radius and therefore equal volume, and not considering orbital velocity, the orbital radius of the Moon would increase from 384,000km to 1.98*10^6km.